The philosophy of sex and love : an introduction - Soble, Alan. (St. Paul, MN : Paragon House, 2008)
"This introductory textbook is an overview of the nature and the ethics of the many aspects of sex and love"--Provided by publisher.
The background -- Two projects; the significance of sex and love; secret pictures; sexual pluralism -- A history of the philosophy of sex and love -- The ancients; medieval philosophy; modern philosophy; the twentieth century; contemporary philosophy -- Sex -- Sexual concepts -- Analytic questions; sexual activity; sexual desire; social constructionism; polysemicity (polysemy); sexual sensations -- Sexual perversion -- St. Thomas Aquinas; problems with natural law; psychological perversion; psychiatry and perversion; a conceptual framework -- Sexual ethics -- Contraception; beyond natural law; Immanuel Kant; contemporary Kantian philosophy; utilitarianism; sadomasochism; love -- Sexual politics -- Consent, again; pedophilia; prostitution and marriage; marital rape; compulsory heterosexuality; pornography -- Love -- Varieties of love -- What is love?; love and value; eros and agape; evaluating and assessing love; the fine gold thread; concern and benevolence; union -- Features of love -- Tangles in theories of love; exclusivity; uniqueness; irreplaceability; constancy; reciprocity -- Sex, love, and marriage -- Pauline marriage; the links; sex and love; the death of desire; saving marriage; reasons for monogamy; reasons for marriage -- Gender -- Women and men; gender and sex surveys; heterosexual failure; gendered sexuality; gendered love.
Includes bibliographical references (p. 265-305) and index.
Keywords: Love; Sex; Sexual ethics